Social and Economic Vulnerability of Roma People 2021
DOI: 10.1007/978-3-030-52588-0_14
|View full text |Cite
|
Sign up to set email alerts
|

“I Felt I Arrived Home”: The Minority Trajectory of Mobility for First-in-Family Hungarian Roma Graduates

Abstract: This chapter explores the upward social mobility trajectories, and the corollary prices of them for those 45, first-in-family college educated Roma in Hungary who come from socially disadvantaged and marginalised family and community background. We argue that among the academically high-achieving participants of our study the most common upward mobility trajectory, contrary to the common belief of assimilation, is their distinctive minority mobility path which leads to their selective acculturation into the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…Previous research shows that among academically high-achieving Roma the most common upward mobility trajectory, contrary to the common belief of assimilation, is their distinctive minority mobility path which leads to their selective acculturation into the majority society (Durst-Bereményi 2021). This distinctive incorporation into the mainstream is close to what the related academic scholarship calls the 'minority culture of mobility' (Neckermann-Carter-Lee 1999).…”
Section: Social Mobility and Race/ethnicitymentioning
confidence: 88%
“…Previous research shows that among academically high-achieving Roma the most common upward mobility trajectory, contrary to the common belief of assimilation, is their distinctive minority mobility path which leads to their selective acculturation into the majority society (Durst-Bereményi 2021). This distinctive incorporation into the mainstream is close to what the related academic scholarship calls the 'minority culture of mobility' (Neckermann-Carter-Lee 1999).…”
Section: Social Mobility and Race/ethnicitymentioning
confidence: 88%
“…The common experience of discrimination along with a strong feeling of solidarity towards the group of origin seem to be common in the narratives of upwardly mobile members of racialized minorities across different countries (Naudet 2018). To cope with this distinctive problem, upwardly mobile minority middle classes develop the repertoire of a so called 'minority culture of mobility' (Neckerman et al 1999), or as we prefer to call it in the case of our Roma first-in-family respondents, the 'minority mobility trajectory' (Durst-Bereményi 2021). A part of this repertoire is the ethos of mobility to 'give back' to one's community of origin by working in a segmented part of the labour market where one deals with 'Roma Issues'.…”
Section: The Price Of Upward Mobility and The Minority Mobility Trajectorymentioning
confidence: 99%
“…They highlighted the tangible and hidden obstacles (like discrimination, prejudice, low self-esteem and self-confidence) that highly educated young Roma have to struggle with during their career. Durst and Bereményi (2021) examined the upward mobility trajectories and its costs of first in family Roma graduates from socially disadvantaged background. They found that they realise a distinctive minority mobility path that results in their selective acculturation into the majority society.…”
Section: Research On Successful Roma In Hungarymentioning
confidence: 99%
“…When she was asked about why she applied for the interview, she said that she was interested in the reasons for her giving up her academic carrier and believed that she climbed too high on the social ladder and she felt as a 'fish out of water', so she had to leave her job in order to decrease the effects of the hysteresis. (see Friedman 2016, Mallman 2018, Bereményi -Durst 2021:…”
Section: "I Was Scared Of Them [Our Colleagues] Yeah Then It Came To ...mentioning
confidence: 99%
See 1 more Smart Citation